2013
DOI: 10.1002/ardp.201200440
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Total Synthesis and Biological Activities of 6‐Deoxyisojacareubin

Abstract: 6-Deoxyisojacareubin was directly synthesized in a six-step route with an overall yield of about 20%. In this route, the excellent site selectivity of this Claisen rearrangement-cyclization reaction cascade was achieved by inserting a bulky p-tosyl group into the free 1-OH, and in the last step, some efficient demethylation methods were explored. Furthermore, all synthesized intermediates including 6-deoxyisojacareubin were evaluated for their inhibitory activity against the QGY-7703 cell line. Of these, compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For ISJ synthesis, the construction of the xanthone nucleus and the benzopyran ring were performed based on our previous work 33 34 . The retrosynthetic analysis of ISJ is outlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For ISJ synthesis, the construction of the xanthone nucleus and the benzopyran ring were performed based on our previous work 33 34 . The retrosynthetic analysis of ISJ is outlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, a new series of derivatives of phenyl-substituted polyoxygenated xanthone were synthesized and evaluated for in vitro cytotoxicity against HCC cells and hepatocytes 33 34 . In the present study, ISJ and compound 7 demonstrated potency at several cellular-level activities, thereby supporting the derivatives’ antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2,2‐dimethyl‐2 H ‐chromene motif is widely found in natural products [1] as bioactive fragments, such as 6‐deoxyisojacareubin (anti‐tumor), [2] inophyllum B (anti‐HIV), [3] deguelin (ubiquinone oxidoreductase) [4] and pongapinone A (anti‐inflammatory) [5] (Figure 1). Due to their promising biological activities, the development of practical synthetic methodologies to chromene fragments has attracted considerable interest [6] .…”
Section: Introductionmentioning
confidence: 99%